PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN VISIONER, DAN MOTIVASI BERPRESTASI TERHADAP PRODUKTIVITAS KERJA GURU (Study Empiris dan Analisis Sitorem Terhadap Guru ASN Sekolah Dasar Di Kecamatan Karawang Barat Kabupaten Karawang): Empirical Study and Sitorem Analysis of Public Elementary Teachers - Sulis Ekowati; Herfina; Karmila, Nita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Researchers focused on teacher work productivity as the dependent variable. Organizational culture, visionary leadership, and achievement motivation as independent variables. The unit of analysis in this research is ASN teachers at State Elementary Schools in West Karawang District, Karawang Regency, West Java. This research uses a quantitative research approach, which is a process of finding knowledge that uses data in the form of numbers as a tool to find information about what we want to know. The method used in this research is a survey method with a path analysis approach. The population in this study were all ASN teachers in state elementary schools in West Karawang District, Karawang Regency, totaling 843 teachers. The total research sample was 271 teachers. The research results show that there is a positive and significant influence of Organizational Culture, Visionary Leadership, and Achievement Motivation on teacher work productivity. Keywords: Organizational Culture, Visionary Leadership, Achievement Motivation, Work Productivity